Comparing alternative Rasch-based methods vs raw scores in measuring change in health. - Norquist, J; Fitzpatrick, R; Dawson, J; Jenkinson, C (2004)
OBJECTIVES: To compare alternative Rasch-based approaches to the assessment of change over time through the example of an outcome measure used in total hip replacement surgery. SUBJECTS: Preoperative data were collected on 1424 patients receiving total hip replacement surgery; 1221 (86%) were sent follow-up questionnaires 1 year after surgery. MEASURES: The 12-item Oxford Hip Score (OHS) questionnaire administered preoperatively and 1-year postoperatively. METHODS: Subscales of the OHS for pain and functional impairment were examined for unidimensionality and item invariance. Two criteria were used to examine Rasch-based measurement of the 2 subscales. Advantages of Rasch measurement were examined in terms of whether it produced improved discrimination of outcomes of patients (1) undergoing different levels of complexity of surgery; and (2) reporting different retrospective judgments of the success of their surgery. Using the method of relative precision in relation to groups of patients distinguished in these 2 ways, change scores using Likert scoring methods were compared with 2 Rasch scoring methods: (1) separate analyses of the 2 time points; and (2) a common scale analysis obtained by stacking patients from the 2 time points. RESULTS: Less evidence for item invariance over time was found for the pain subscale. Other evidence supported treating subscales as unidimensional. Whichever Rasch scoring method was used, some gains in precision over standard Likert scoring were obtained in discriminating between groups of patients. CONCLUSIONS: The evidence from the current study suggests that there may be some gains in sensitivity to change of outcome measures from different Rasch-based scoring approaches.